(untitled) (Vietnam Journal of Community Medicine, 2022)
Malignant Peripheral Nerve Sheath Tumors (MPNSTs) are rare, high-grade soft tissue sarcomas of extranodal origin and often metastasize early. The World Health Organization has coined the term MPNST to replace previously heterogeneous and often confusing terms, such as malignant schwannoma, malignant neurilemmoma, neurogenic sarcoma and neurofibrosarcoma. MPNSTs arise from the sheaths of peripheral nerve fibers, either from Schwann cells or from neural crestderived pluripotent cells. Schwann cells are believed to be responsible for the formation of benign as well as malignant tumors in the nerve fiber sheath. MPNST can appear in many places in the body, but in the lungs is extremely rare. Imaging is usually nonspecific. The diagnosis was confirmed by immunohistochemistry. We report a case of MPNST in the lung, with spinal metastases; was confirmed by biopsy of metastatic lesions and immunohistochemistry at the National Lung Hospital.